2018
DOI: 10.1111/jerd.12377
|View full text |Cite
|
Sign up to set email alerts
|

Low‐level laser therapy as an adjunct to connective tissue graft procedure in the treatment of gingival recession defects: A systematic review and meta‐analysis

Abstract: Gingival recessions in dentistry are of major esthetic concern. Minimal gingival recessions can be treated by flap operations, but the predictability and stability of the outcomes is debatable. In the present review, low level laser therapy (LLLT) adjunct to connective tissue graft (CTG) depicted a significant improvement in the predictability and stability of root coverage outcomes compared with CTG alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 39 publications
(109 reference statements)
0
7
0
Order By: Relevance
“…The combination use of PRF showed no evident benefits in terms of MRC or CAL, but significantly increased width of keratinized tissue (KTW) compared with CAF + CTG (Moraschini & Barboza Edos, 2016). The meta-analysis of four randomized controlled trials (RCT) showed the adjunct use of lowlevel laser therapy (LLLT) to CAF + CTG depicted an improvement of clinical and patient-centred outcomes (Akram, Vohra, & Javed, 2018).…”
mentioning
confidence: 99%
“…The combination use of PRF showed no evident benefits in terms of MRC or CAL, but significantly increased width of keratinized tissue (KTW) compared with CAF + CTG (Moraschini & Barboza Edos, 2016). The meta-analysis of four randomized controlled trials (RCT) showed the adjunct use of lowlevel laser therapy (LLLT) to CAF + CTG depicted an improvement of clinical and patient-centred outcomes (Akram, Vohra, & Javed, 2018).…”
mentioning
confidence: 99%
“…LLLT adjunct to connective tissue graft depicted a significant improvement in the predictability and stability of tissue healing outcomes compared with connective tissue graft alone. 12 Thus, in this case report, LLLT adjunct to connective tissue grafts was applied to increase sufficient labiolingual width and apicocoronally thickness that were required for housing the pontic. Following removal of the failed implant, the bone resorbs and may lead to the collapse of residual bucco-palatal tissues.…”
Section: Discussionmentioning
confidence: 98%
“…The collection of autogenous palatine grafts results in an increase in the number of surgical sites, corresponding to a donor and a recipient area, which results in a longer time required in the surgical procedure, discomfort to the patient, and greater risks of paresthesia, changes in donor site sensitivity, necrosis, infectious processes, bleeding and damage to the major palatine artery. However, the achievement of an ideal palatal subepithelial connective graft, through established clinical requirements, is aimed at achieving stability of the gingival profile, with significant aesthetic and functional improvements in areas of apical migration of marginal gingival tissues [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%